BL_GERICHTE 731 12 385 / 80 vom 18. April 2013 , Entscheid des Kantonsgerichts Basel-Landschaft, Abteilung Sozialversicherungsrecht vom 18. April 2013 (731 12 385 / 80) - BL Gerichte (2013)
Leistungen